Rhizomatic transformation An act of observation from the perspective of useful knowledge for social change (Ágora de Heterodoxias, 2024)
Ágora de Heterodoxia begins its tenth year of publications, generating work alliances based on everyday practice. Consequently, throughout the editorial process of this issue, we are accompanied as co-editor by Dr. López who, as a researcher in the area of Development Studies, a specialist of recognized international academic prestige - linked to the Center for Development Studies, Cendes, of the Central University of Venezuela - co-directed the editorial work. From this modality of partial leadership, we manage to produce an invitation to present communications focused on three fundamental dimensions for development studies: a) o human, b) o social and c) at decision making, in the perspective that the Sciences to Development is concerned with the processes of social change and the factors that affect our countries.
Keywords: Rhizomatic transformation; useful knowledge; social change; work alliances